2004
DOI: 10.1021/jm049695v
|View full text |Cite
|
Sign up to set email alerts
|

A Docking Score Function for Estimating Ligand−Protein Interactions:  Application to Acetylcholinesterase Inhibition

Abstract: Acetylcholinesterase (AChE) inhibition is an important research topic because of its wide range of associated health implications. A receptor-specific scoring function was developed herein for predicting binding affinities for human AChE (huAChE) inhibitors. This method entails a statistically trained weighted sum of electrostatic and van der Waals (VDW) interactions between ligands and the receptor residues. Within the 53 ligand training set, a strong correlation was found (R 2 ) 0.89) between computed and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…[47] Given that the role of water molecules in the AChE binding site is not completely understood, docking simulations were performed without taking water molecules into account. [48] The target proteins were prepared by adding hydrogen atoms, completing and optimizing missing residues, removing water and the co-crystallized molecules. The basic amino groups were protonated, aromatic amino functional groups were left uncharged, and carboxylic groups were considered to be deprotonated.…”
Section: Docking Simulationsmentioning
confidence: 99%
“…[47] Given that the role of water molecules in the AChE binding site is not completely understood, docking simulations were performed without taking water molecules into account. [48] The target proteins were prepared by adding hydrogen atoms, completing and optimizing missing residues, removing water and the co-crystallized molecules. The basic amino groups were protonated, aromatic amino functional groups were left uncharged, and carboxylic groups were considered to be deprotonated.…”
Section: Docking Simulationsmentioning
confidence: 99%
“…Although, many comparative molecular docking studies have been reported for AChE [40][41][42][43][44], the reported findings were devoid of the comments regarding conserved water molecules in the active site of AChE, which can mediate the interaction between amino acid side chains and inhibitors. Similarly probable conformations of Phe330 during docking procedure were also neglected.…”
Section: Introductionmentioning
confidence: 98%
“…Given an increasingly sizable body of screening data for the MetAP enzyme, our plan is to train a comparative binding energy (COMBINE) type model to specifically represent the idiosyncrasies of the MetAP inhibitor structure-activity relationship. We have previously found this to be highly successful in studies of other complex receptors such as acetylcholinesterase 26 and adenylyl cyclase. 27 The compounds reported herein were evaluated in silico according to standard oral availability and absorptiondistribution-metabolism-excretion (ADME) criteria, using SYBYL 28 and VolSurf 29 programs.…”
Section: Resultsmentioning
confidence: 98%